Mansi Lexical Materials in the Manuscript Heritage of the Russian Academician Gottlieb Siegfried Bayer (1694–1738) - Tatiana Nikolaevna Dmitrieva (Известия Уральского федерального университета. Серия 2: Гуманитарные науки)
This article analyses the Mansi vocabulary from the handwritten Latin-Tatar-Vogul dictionary kept in Glasgow (Great Britain), in the archive of the Russian academician Gottlieb Siegfried Bayer (1694–1738), which has never been done before. Bayer’s scholarly heritage is of great interest and has not been sufficiently studied yet. The author manages to establish that Bayer’s dictionary is a partial list of lexical materials compiled by another Russian academician, Gerhard Friedrich Mьller (1705–1783), Head of the Academic Unit of the Second Kamchatka (Great Northern) Expedition (1733–1743). It is also established that these Mansi (Vogul) materials were recorded by Müller in Tobolsk in 1734 from a native speaker of the Pelym dialect and preserved in Mьller’s archive in the Russian State Archive of Ancient Acts (RGADA) in Moscow. A comparison of Bayer’s and Mьller’s dictionaries shows that Bayer copied only the most interesting lexemes from Müller — 90 Vogul words, while Müller has about 300 of them. Most of the words copied by Bayer are reflected in lexicographic sources, which makes it possible to trace their correspondences in Mansi dialects, as well as to identify lexical parallels. The article considers several lexemes that are of the greatest interest from the point of view of semantics and word formation. More particularly, the name of the kopeck uses the designation of a ‘squirrel’ as a monetary unit in Siberia, hence ‘rouble’ (Schдtlin) is ‘one hundred kopecks’, or ‘one hundred squirrels’; in the name оf paper, the Mansi ‘birch bark’ (-schasch) is added to the word of Komi origin ‘paper’ (nepag). Additionally, the author reveals lexemes that are not marked in dictionaries or have other semantics, i.e. the name of the ‘water spirit’ (Uнtkas) is used to denote ‘the devil’; the adverb ‘above’ (Nùmna) is used to denote ‘the sky’; the month as a period of time is denoted by ‘four weeks’ (Nille-Sat); ‘the cloudberry colour’ (Morochoschp) juxtaposition is used to denote ‘yellow’. Finally, the article mentions some inaccuracies made by Bayer when copying Mьller’s dictionary.